KEMAMPUAN PEWARNAAN ZIEHL-NEELSEN DAN FITE FARACO UNTUK MENDETEKSI MYCOBACTERIUM SP. PADA SAMPEL JARINGAN : A LITERATURE REVIEW - Dwi Putri, Riska; Agustina, Hasrayati; Usman, Hermin Aminah (Majalah Patologi Indonesia, 2025)
Histopathology is an essential method for disease diagnosis. It is crucial for clinicians to have an ideal diagnostic method that is simple, specific, and highly sensitive. The sensitivity and specificity of a test can be determined by comparing it with other tests. Tuberculosis is an infectious disease caused by Mycobacterium tuberculosis. Mycobacterium tuberculosis is diagnosed using Ziehl-Neelsen staining, which dif erentiates acid-fast bacilli from non-acid-fast bacilli. The Fite Faraco staining technique is used to detect Mycobacterium sp in tissue specimens. All reviewed articles show that Ziehl-Neelsen staining has a sensitivity between 21% - 97.6%, specificity between 85.7% - 92%, NPV between 34.3% - 75%, PPV between 30.9% - 100% in detecting Mycobacterium sp in tissue samples. Fite Faraco staining shows a sensitivity between 50% - 74.6%, specificity between 84% - 100%, NPV between 33.6% - 56.7%, PPV 38.1% in detecting Mycobacterium sp in tissue samples.It is detected that Ziehl-Neelsen and Fite Faraco can be used to detect bacteria, Mycobacterium sp especially bacteria Mycobacterium tuberculosis and Mycobacterium leprae. However, Ziehl-Neelsen staining has better ability in terms of sensitivity, PPV, and NPV than Fite Faraco in detecting bacteria Mycobacterium sp, especially Mycobacterium tuberculosis. As Fite-Faraco staining is superior in terms of specificity. Other things that must be Considered in carrying out Ziehl-Neelsen and Fite Faraco staining are specific types of samples, making modifications such as modifying microwave heating on the Ziehl-Neelsen staining method and combining examination with H&E staining and multiplex PCR to increase the validity of the two staining methods.